ADDRESSING THE POOR AKHLAK OF CHILDREN FROM THE PERSPECTIVE OF ISLAMIC EDUCATION TEACHERS: A CASE STUDY - Abdullah, Nik Md Saiful Azizi Nik; Din, Siti Adawiah; Isa, Rabi'atul Athirah Muhammad (The journal of contemporary issues in business and government, 2021)
School children nowadays are facing moral decay and the issues of akhlak. This study attempted to investigate the issue of akhlak development among school children raised by single parents at a primary school and topropose ways of addressing the harmful effects of single parenting on students’ akhlak. The study employed a qualitative method in which data were collected via in depth interview. The respondents of the study consisted of two Islamic education teachers. Generated in the form of interview transcripts, the data were thematically analysed in addition to the observation notes, resulting in the identification of several themes and subthemes. The findings revealed that the prevailing themes in relation to the effect of single parenting on children’s akhlak include role of teachers, school initiatives, peer influence, parental involvement. The teachers, on the other hand, recommended strategies which consider teachers’ role such as implementation of targhib and tarhib method according to the Qur'an,make the Prophet PBUH as the best role model, taking ibrah from al-Quran by storytelling and implement the process of ta’aruf, tafahum, ta'awun and takaful. Besides school initiatives, peer influence and parental involvement also play a role to effectively address the subject of akhlak deterioration among the school children. The findings of this study are beneficial to relevant stakeholders such as teachers, parents, and the students themselves in addressing the harmful effects of single parenting on students’ akhlak.